Esophageal stent migration: Testing few hypothesis with a simplified mathematical model. (1st December 2016) - Garbey, Marc; Salmon, Remi; Fikfak, Vid; Clerc, Claude O.
Abstract: Esophageal stent placement has significantly improved the quality of life in patients with malignant as well as benign esophageal obstructing lesions. Despite its early success and rapid adoption, stent migration still occurs in as many as 30% of cases especially with fully covered stents. To date, few models of interaction between the stent and the esophageal wall have been published and these have only focused on the deployment of the stent or the static mechanical stress distribution of the stent material. To elucidate the mechanism behind esophageal stent migration we developed a simplified radially symmetric computational model of esophageal peristalsis and the stent. A thorough review of the literature on esophageal peristalsis was performed and pertinent data were implemented into the model. Similarly, mechanical properties of an existing esophageal stent were used for the stent model. A sensitivity analysis of the parameters of the model enabled identification of the key elements of stent design that influence the degree of stent migration including flares design, stent length as well as longitudinal and radial stiffness. A comparison of the model to the migration rate reported in clinical studies for various types of fully covered stents further verified our model, which can significantly contribute to the development of a more stable esophageal stent with lower rates of migration. Highlights: A simplified model of the esophagus and the esophageal stent is proposed. The model of the esophagus during peristalsis was verified against literature data. The Migration rate of different stent designs was verified against clinical trials. The non-linearity between the stent design and its migration rate was highlighted.